Social identity in network formation - Ying Chen; Tom Lane; Stuart Macdonald (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2024)
Using a laboratory experiment, we study the evolution of economic networks in the context of fragmented social identity. We create societies in which members can initiate and delete links to others, and then earn payoffs from a public goods game played within their network. We manipulate whether the society initially consists of segregated or integrated identity groups, and vary whether societal mobility is high or low. Results show in-group favouritism in network formation. The effects of original network structure are long-lasting, with initially segregated societies permanently exhibiting more homophilic networks than initially integrated ones. Moreover, allowing greater social mobility results in networks becoming less rather than more integrated. This occurs in part because eviction from networks is based on out-group hostility when societal mobility is high, and on punishing free riders when mobility across groups is low.
Keywords: C92; D85; D91; Z13; 330; Social identity; Social network; In-group bias; Homophily; Laboratory experiments